Specialist palliative care improves the quality of life in advanced neurodegenerative disorders: NE-PAL, a pilot randomised controlled study. Issue 2 (16th July 2015) - Veronese, Simone; Gallo, G; Valle, A; Cugno, C; Chiò, A; Calvo, A; Cavalla, P; Zibetti, M; Rivoiro, C; Oliver, D J
Abstract : Background: This study analysed the impact on palliative care outcomes of a new specialist palliative care service for patients severely affected by amyotrophic lateral sclerosis (ALS/MND), multiple sclerosis, Parkinson's disease and related disorders (multiple system atrophy progressive supranuclear palsy, MSA-PSP). Methods: The design followed the Medical Research Council Framework for the evaluation of complex interventions. A phase II randomised controlled trial (RCT) was undertaken comparing an immediate referral to the service (FT, fast track) to a 16-week wait (standard track (ST), standard best practice) using a parallel arm design. The main outcome measures were Quality of Life (measured with Schedule for the Evaluation of Individual Quality of Life Direct Weight, SEIQoL-DW) and burden of the carers (Caregivers Burden Inventory, CBI), with secondary outcomes of symptoms, psychosocial and spiritual issues. Results: 50 patients severely affected by neurodegenerative conditions and their informal family carers were randomised: 25 FT, 25 ST. At baseline (T0), there were no differences between groups. 4 patients died during the follow-up (2 FT, 2 ST) and 2 FT patients dropped out before the end of the study. After 16 weeks (T1), FT participants scored significant improvement in the SEIQoL-DW index, pain dyspnoea sleep disturbance and bowel symptoms. Conclusions: This exploratory RCT provides evidence that no harm was experienced by SPCS for patients severely affected by neurodegenerative disorders. There was an improvement in quality of life and physical symptoms for neurological patients in palliative care. Caregiver burden was not affected by the service.